Spatial-temporal changes of landscape ecological risk in the Liuchong river basin from the perspective of production-life-ecological space - Ren, Jintong; Dong, Yanqin; He, Panxing; Lu, Hanyu (Frontiers in Environmental Science, 2024)
Promoting the construction of ecological civilization and sustainable development in karst mountainous areas by analyzing the spatial and temporal changes of landscape ecological risks is critical in karst mountainous watersheds. In this study, the land use transfer matrix, landscape ecological risk evaluation model, ecological contribution rate of land use change, and spatial autocorrelation analysis were combined to quantitatively analyze the land use and landscape ecological risk of a typical karst watershed, Liuchong River Basin, over the past 20 years.The results revealed that: (1) From 2000 to 2020, the functional classification of land use in the Liuchong River Basin was dominated by the woodland ecological space, and the most significant shifting characteristics were the increase in the area of watershed ecological space and industrial production space and the decrease in woodland ecological space, with shifts in the middle reaches of the Liuchong River being the most drastic; (2) Generally, the change of the regional landscape pattern was related to the transformation of the land use function type of "production-life-ecological space," and the spatial aggregation of ecological risk level showed a gradual weakening trend. (3) The conversion of the watershed ecological space to the grassland ecological and agricultural production spaces, the conversion of urban living space to the agricultural production space, and the conversion of the rural living space to the agricultural production space were the dominant factors affecting ecological improvement, whereas the conversion of the woodland ecological space to the grassland ecological space, the woodland ecological space to the agricultural production space, and the grassland ecological space to the agricultural production space contributed to ecological degradation. The study findings can be used as a reference for the coordinated development of "production-life-ecological space" in karst watersheds and provide a scientific basis for ecological environmental protection and sustainable utilization.